Development of an Online Multiplayer RTS Video Game for Windows PC - Gonzales, André G. (2023)
In recent years, the video game industry has experienced significant growth, as a large portion of the global population has turned to gaming as a pastime during the COVID-19 pandemic. However, not all genres of video games have been part of this surge in popularity. This is the case for real-time strategy (RTS) games, whose popularity has been declining over time, despite the cognitive benefits they offer, such as improved information processing and visual cognitive enhancement. Therefore, the development of a multiplayer real-time strategy game for Windows PC called “Cosmic Crusade” is proposed. This game is designed to provide a quick understanding of its mechanics and gameplay. This article outlines the development procedures for the Cosmic Crusade video game and includes validation efforts aimed at confirming and ensuring user satisfaction with the game. © 2023 CISCI 2023 - Vigesima Segunda Conferencia Iberoamericana en Sistemas, Cibernetica e Informatica, Vigesimo Simposium Iberoamericano en Educacion, Cibernetica e Informatica, SIECI 2023 - Memorias.